Recreation of ethno-cultural markers in the translations of “Blood and Sweat” - Zhussupova, Akbota; AshimkhanovаSvetlana (Opción, 2020)
Associated with the globalization of cultural space, the problem of understanding, functioning, and development of ethno-cultural identity is becoming one of the most urgent today, all over the world. The purpose of the research is to carry out a complex analysis of ethno-cultural components contained in the literary work and to study the mechanisms of their transformation during translation, to establish their adequacy. The wide spectrum of lexical units, reflecting ethno-cultural specificity of the Kazakh people is not typical for either Russian or English speaking audiences.